Study Protocol - Accurate assessment of kidney function in Indigenous Australians: aims and methods of the eGFR Study - Panagiotopoulos Sianna; Drabsch Katrina; Ward Leigh C; Piers Leonard S; Thomas Mark AB; Sinha Ashim K; MacIsaac Richard J; Cass Alan; Hoy Wendy; Ellis Andrew G; Jones Graham RD; Sharma Suresh K; et al. (BMC, 2010)
Abstract Background There is an overwhelming burden of cardiovascular disease, type 2 diabetes and chronic kidney disease among Indigenous Australians. In this high risk population, it is vital that we are able to measure accurately kidney function. Glomerular filtration rate is the best overall marker of kidney function. However, differences in body build and body composition between Indigenous and non-Indigenous Australians suggest that creatinine-based estimates of glomerular filtration rate derived for European populations may not be appropriate for Indigenous Australians. The burden of kidney disease is borne disproportionately by Indigenous Australians in central and northern Australia, and there is significant heterogeneity in body build and composition within and amongst these groups. This heterogeneity might differentially affect the accuracy of estimation of glomerular filtration rate between different Indigenous groups. By assessing kidney function in Indigenous Australians from Northern Queensland, Northern Territory and Western Australia, we aim to determine a validated and practical measure of glomerular filtration rate suitable for use in all Indigenous Australians. Methods/Design A cross-sectional study of Indigenous Australian adults (target n = 600, 50% male) across 4 sites: Top End, Northern Territory; Central Australia; Far North Queensland and Western Australia. The reference measure of glomerular filtration rate was the plasma disappearance rate of iohexol over 4 hours. We will compare the accuracy of the following glomerular filtration rate measures with the reference measure: Modification of Diet in Renal Disease 4-variable formula, Chronic Kidney Disease Epidemiology Collaboration equation, Cockcroft-Gault formula and cystatin C- derived estimates. Detailed assessment of body build and composition was performed using anthropometric measurements, skinfold thicknesses, bioelectrical impedance and a sub-study used dual-energy X-ray absorptiometry. A questionnaire was performed for socio-economic status and medical history. Discussion We have successfully managed several operational challenges within this multi-centre complex clinical research project performed across remote North, Western and Central Australia. It seems unlikely that a single correction factor (similar to that for African-Americans) to the equation for estimated glomerular filtration rate will prove appropriate or practical for Indigenous Australians. However, it may be that a modification of the equation in Indigenous Australians would be to include a measure of fat-free mass.